Conflict of legal principles in drug crimes by children: Analysis of judges' discretion in cumulative decisions - Rizky Wibowo; Nahar Surur; Lia Indah Khilmina (Privietlab, 2025)
This research analyzes the conflict of principles in juvenile criminal law, particularly in relation to the imposition of cumulative punishment on juveniles who commit narcotic offences. The paradigm of child protection in the Child Criminal Justice System Law (UU SPPA), which prioritizes restorative justice and the ultimum remedium principle, is confronted by the samenloop principle of the Criminal Code and the classification of drug offences as extraordinary crimes. Through a deductive approach, the discussion identifies inconsistencies in judicial practice. Findings from several case studies show that judges often use discretion to impose cumulative punishments, overriding the mandate of the SPPA Law to prioritize rehabilitation over retribution. This conflict indicates a misalignment between legal ideals and practical implementation, rooted in rigid legal interpretations and normative lacunae. Therefore, this research recommends fundamental solutions, namely, the affirmation of the lex specialis principle that places the SPPA Law above the general law, the reinterpretation of extraordinary crime as a call for extraordinary rehabilitation, and the strengthening of binding decision guidelines for judges (SEMA). Judges' discretion must be directed towards a philosophical understanding that true justice for children is an opportunity for recovery, not a punishment that robs them in their future. Thus, the integrity of the juvenile criminal justice system could be upheld.